PERCEPTION OF POLITICAL NEWS AMONG STUDENTS AT PHANOM BENCHA SCHOOL, KHAO PHANOM DISTRICT, KRABI PROVINCE - Phahukarn, Nuengruethai; Suvadฺdฺho (Sookpanich), Phrakrupalad Athit (Journal of MCU Nakhondhat, 2024)
The purposes of this research article are to 1) study the level of political news awareness among students at Phanom Bencha School 2) study ways to develop political news awareness among students at Phanom Bencha School, Khao Phanom District, Krabi Province. It is mixed methods research. Sample group 1) Quantitative research, including 250 students at Phanom Bencha School, systematic random sampling. 2) Qualitative research. Important informant Using a purposive sampling method, there were 5 people. Research tools Questionnaires were used in quantitative research. and use in-depth interviews in qualitative research Collection of quantitative research data Questionnaires were distributed to the sample group and the questionnaires were collected back by themselves. and qualitative research Key informants were interviewed in-depth interviews in person. Statistics used for research and data analysis include frequency, percentage, mean, and standard deviation. and descriptive analysis. The research results found that the level of political news awareness of students at Phanom Bencha School. Overall it is at a high level. in each aspect is at a high level and 2) there are guidelines for developing political news awareness of students at Phanom Bencha School, Khao Phanom District, Krabi Province. In terms of television media, it is classified into 5 types: 1) Television services should be provided so that students can access the media. political news along with promoting public relations 2) Presenting television media in the classroom Encourage them to watch political news before going to class. and summarize what has been viewed before learning in various subjects. 3) News analysis critically to understand various perspectives Ponder and analyze the information by yourself. 4) Create motivation. Make students want to follow the news on television and compare it with other media.